PERANCANGAN ANTARMUKA SISTEM PENDATAAN PENGUNJUNG BERBASIS WEBSITE DI KANTOR PERBEKEL DESA UNGASAN - Ni Luh Eka Suryaningsih; I Ketut Gede Suhartana; I Made Widhi Wirawan (Jurnal Pengabdian Informatika, 2025)
In the dynamic digital era, the adoption of information technology is crucial to enhance efficiency and transparency in public services at the village level. The web-based visitor registration system at the Office of the Village Chief in Ungasan Village serves as a successful implementation example in this effort. The manual processes proved inefficient and time-consuming, prompting the progressive step of technology adoption. This research documents and analyzes the development of the system, employing a comprehensive approach from needs analysis to evaluation. The result is an intuitive and responsive web application for users, improving village administration efficiency. The system's advantage lies in its ease of access and use by the community, enhancing transparency in public services. Thus, this research contributes significantly to the development of a visitor registration system focused on optimal user experience and enhanced efficiency in public services at the village level.